2016
DOI: 10.1155/2016/8168943
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Roles of Biological Bone Constructed with Peripheral Blood Derived EPCs and BMSCs in Osteogenesis and Angiogenesis

Abstract: This study aimed to determine the possible potential of partially deproteinized biologic bone (PDPBB) seeded with bone marrow stromal cells (BMSCs) and endothelial progenitor cells (EPCs) in osteogenesis and angiogenesis. BMSCs and EPCs were isolated, identified, and cocultured in vitro, followed by seeding on the PDPBB. Expression of osteogenesis and vascularization markers was quantified by immunofluorescence (IF) staining, immunohistochemistry (IHC), and quantitive real-time polymerase chain reaction (qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
5
19
0
Order By: Relevance
“…The expression of major markers of bone differentiation i.e. Opn, Col I and Ocn are linked with the maturation of osteoblasts and bone development [46]. The degree of Ocn expression was significantly more in grad.250.top scaffolds which promoted more bone formation and mineralization in this scaffold structure.…”
Section: Discussionmentioning
confidence: 92%
“…The expression of major markers of bone differentiation i.e. Opn, Col I and Ocn are linked with the maturation of osteoblasts and bone development [46]. The degree of Ocn expression was significantly more in grad.250.top scaffolds which promoted more bone formation and mineralization in this scaffold structure.…”
Section: Discussionmentioning
confidence: 92%
“…The use of MSCs/EPCs co-culture is an effective method to generate osteogenic differentiation. In our previous study, we demonstrated that EPCs enhanced MSC osteogenesis in vivo [27], and similarly report also showed that MSCs coculture with EPCs promoted significant osteogenic differentiation, when compared with in vivo MSCs monoculture [19].…”
Section: Discussionmentioning
confidence: 53%
“…Previous study showed that endothelial differentiation of MSCs only occurs in direct co-culture systems, whereas MSCs maintain their initial biological properties in in-direct culture conditions [38,39]. Abundant studies have demonstrated that factors generated by EPCs are considered crucial for the process of osteogenesis, suggests that paracrine signaling was sufficient to promote MSCs differentiation [19]. MAPKs play important roles in controlling cell proliferation, and are involved in multiple cellular pathways and functions [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible source of lipid formation within the bone marrow is the disrupted balance between osteogenesis and adipogenesis of BMMSCs, and the latter assumes predominance [ 2 , 3 ]. BMMSCs, the most important MSCs in the bone morrow, are self-renewable, multipotent stem cells with the capacity to differentiate into cartilage, bone, and adipose tissue [ 4 6 ]. The contributing factors of the formation of osteoblasts are recognized as an inhibitor for the maturation of adipocytes and vice versa [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%